Estimation of medical costs for ischemic stroke patients - from the perspective of a health care provider - Noriza Majid,; Chew, Yee Lin; Azimatun Noor Aizuddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The increasing prevalence of stroke has presented challenges to all countries. Since 2007, stroke has been one of the leading causes of death in Malaysia. Furthermore, the number of strokes is expected to increase steadily. Certainly, all parties are concerned, particularly considering the socioeconomic burden that must be borne. As a result, the community and health-care providers must measure the number required to cover the medical expenses associated with a stroke. The estimated medical costs are based on the medical costs of ischemic stroke patients treated at Hospital Canselor Tuanku Mukhriz, which involved a total of 2161 stroke patients between 2016 and 2020. Demographic factors such as age and gender, as well as clinical factors such as severity, length of stay (LOS), and comorbid factors, were used to determine the medical costs of ischemic stroke patients. A logarithmic transformation was carried out on the medical cost to create a more suitable medical cost estimating model, considering the skewed nature of the medical cost data of ischemic stroke patients. As a result of the multiple linear regression analysis, age, LOS, severity level, type of comorbidity such as hypertension, ischemic heart disease (IHD), atrial fibrillation (AF), smoking and alcohol habits were found to have a significant effect on these medical costs. However, a patient’s medical costs are unaffected by gender or type of comorbidity, such as diabetes or hyperlipidemia. Furthermore, it was discovered that increased LOS, severity levels, or the presence of comorbidities such as IHD, AF, and smoking habits all increased patients’ medical costs. Medical costs, on the other hand, were found to be lower in patients who were older, consumed alcohol, and had hypertension.